LEARNING MANAGEMENT IN REALIZING WORSHIP INDEPENDENCE IN NEW STUDENTS - Tamam, Badrud; Ruhita, Ruhita; Ibrahim, Abdullah; Farihin, Ahmad; Aminudin, Aminudin (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: Islamic boarding schools play a crucial role in shaping students' religious practices and independence, especially among new students from diverse backgrounds. Purpose: This study examines the role of learning management in fostering religious independence among new students at the Bolon Islamic Boarding School. It addresses the challenges faced by the institution in encouraging students from various religious backgrounds to perform obligatory worship independently. Method: Using a qualitative descriptive approach, data were collected through participant observation, interviews, and document analysis. Result: The study found that structured learning management, particularly consistent congregational prayers led by a respected Kiai and focused fiqh lessons, significantly improved students' discipline and independence in worship. The findings highlight that effective learning management not only enhances students' understanding of religious practices but also fosters sustainable religious discipline. Conclusion: The study suggests that other Islamic educational institutions could benefit from adopting a similar structured approach